Marketing Communication Through e-WOM Strategy: Case Study in PT. Solusi Senyum Indonesia - Zafirah Quroatun ‘Uyun; Fadhilah Annisa Rahma; Andreas Ryan Sanjaya (Alfuad: Jurnal Sosial Keagamaan, 2024)
Various promotional media are intensified to support the company profile (company image) in order to build reputation and trust in the target market/consumers. The company profile plays an important role in showing identity, by displaying the vision and mission and the products/services offered (Kris Nathan, 2016). The planned strategy must also be considered as well as possible so that it is effective and efficient. According to Henning (2004), E-WoM is a positive or negative review made based on potential, actual and trial results from consumers about a product/service via the internet. In this digital era, E-WoM is one of many marketing communication strategy options and greatly influences consumers' purchasing decisions. In its application some special ethics are required. Furthermore, this journal aims to examine the level of success of the e-WoM strategy and its impact on the company's image using observation methods with qualitative standards resulting from tagging social media platforms and e-commerce. It is hoped that professional communication practitioners within the company and the other will use this strategy as much as possible.